Analisis Pelanggaran Hukum Pidana Khusus Pemalsuan Dokumen Perjalanan Oleh Warga Negara Asing - Fudin, Moh. Zukhruf; Wibowo, Ihwan Nurarif; Yanottama, Muhamad Rian (Wajah Hukum, 2024)
Indonesia is a rich country and has a strategic location because many travelers pass through it, not a few of whom also have bad desires or goals to disrupt the security and order of the sovereignty of the Indonesian territory. Phenomena that are often found in the context of threatening sovereignty can be found in violations of special criminal law such as criminal acts of falsifying travel documents committed by foreign citizens so that they can enter Indonesian territory. It cannot be denied that they could commit criminal acts that cause unrest among the Indonesian people. Alone. Immigration is an official government institution or agency and is responsible for problems related to the entry and exit of people into Indonesia's sovereign territory. Immigration also requires various preventive efforts to be carried out to limit and even eliminate threats from surveillance, investigations and even investigations in order to uphold Indonesia's sovereignty. Immigration always carries out its immigration function based on Article 1 point (3) of Law Number 6 of 2011 concerning Immigration where immigration carries out its duties in immigration services, law enforcement, state security, and facilitator of community welfare development. In determining various actions, immigration always has clear guidelines based on the legal basis that is still valid from both national and international legal grounds because immigration is always related to the international scope.